(3TQM CQLhRI GHf CHj GdQLGds - (3CMeO Hf MSjf Hf Ydj Hf (B((3bfaP(B) (3GdbSWfWjfis; (3Ydj Hf CHj GdQLGd GdTjHGfj, CHh GdMSf GdeZQHj GdbjQhGfj,J (B432 (3g` s ((3Ydi Hf GdbGSe GdeLhd GdMSfi GdaGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb HbOQJg , hejRge HMceJg hHYO aEfg deG cGf SjO GdhRQGA SjOfG CHj jMji GHf SjOfGGdeQMhe CHj eLGgO ZGRi CLd ef NOe HCZdi GdYdhe GdYbdjI bOQkG s
(3BNQgG (B:s
(3hjOd CjVkG Ydi GdUhGYb hGdHQO , dCf GdcGJH eeJRL hGddg CYde hgGgfG GfJgi GdZQV ai gPG GdTQM GdeHGQc , hLGA HMeO Gddg TGedkG cGajI def JOHQgG hCMce CUhdgG s
(3HgG LOGhds
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3HBNQgG Jedc dYdi Hf GdbGSe GdeLhd GdMSfi GdaGSi s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs